Daya Terima Dan Kandungan Gizi Kue Bolu Cukke Subtitusi Tepung Ubi Jalar Ungu - Manjilala, Manjilala; Sirajuddin, Sirajuddin (Jurusan Gizi Poltekkes Kemenkes Makassar, 2018)
Bolu cukke is one of the traditional cake Bugis-Makassar, commonly consumed by the community, especially when enjoying a break. In order for a benefit value of Bolu Cukke, it takes effort to enrich the nutritional content, one of which is to replace wheat flour with sweet potato flour. A pre-experiment research conducted in Food Technology Laboratory of Nutrition Poltekkes Kemenkes Makassar, with number of panelist amoung 50 people. Nutritional content was analyzed using Kjhedal method for protein, gravimetric for fat and titrimetric for carbohydrate. Analyzed by using Kruskal-Wallis and Mann-Whitney test with 95% confidence level. The results showed that the acceptability based on the taste aspect in the four groups was the same (p = 0.275) the sample group was 75% preferred by the panelists. There were color differences in the four sample groups (p = 0,000), when compared with the substituted sample with purple sweet potato flour, the sample group was 50% preferably panelists. There were differences in the flavour in the four sample groups (p = 0.013), the sample group 50% preferred by the panelists. Acceptance based on taste aspect in all four groups was the same (p = 0.733), the sample group was 75% preferred by panelists. The highest protein nutrient content in the 0% sample group, 75% group fat and 75% carbohydrate. This research suggests that Bolu Cukke substitution of purple sweet potato flour is very feasible to be used as an alternative of Complementary Feeding in pregnant mother and toddler.